A Meta-Analysis on the Effects of Problem-Posing in Mathematics Education on Performance and Dispositions. (2nd October 2022) - Wang, Min; Walkington, Candace; Rouse, Amy
ABSTRACT: The purpose of this meta-analysis is to examine the effect of problem-posing on students' mathematical academic outcomes, including problem-solving skills, problem-posing skills, mathematical dispositions, and mathematics achievement. Twenty-one studies that were published between 1990 and 2019 with problem-posing as the intervention were included in the meta-analysis. A random-effects model was employed with robust variance estimation (RVE) to correct for the intercorrelation between effect sizes when necessary. The estimated average standardized mean difference effect size of problem-posing interventions ( g = 0.64) demonstrated that problem-posing had a positive impact on students' academic outcomes. Specifically, across the interventions, students' problem-solving skills and mathematical achievement improved by engaging in problem-posing activities. The moderator analyses revealed that problem-posing interventions were more effective when structured, semi-structured, and free problem-posing tasks were all implemented, and longer-duration intervention was associated with larger improvement in students' mathematical dispositions.